MARK4 regulates NLRP3 positioning and inflammasome activation through a microtubule-dependent mechanism - Xuan Li (Nature Portfolio, 2017)
Microtubules regulate activation of the NLRP3 inflammasome, but the underlying molecular mechanism is unclear. Here the authors show that MARK4 binds NLRP3 and shuttles it to the microtubule-organizing centre to promote optimal inflammasome activation.